Factors Influencing Follicular Output Rate and Follicle-to-Oocyte Index in POSEIDON-Defined Low-Prognosis Women in Vietnam: A Cross-Sectional Study - Le MT; Nguyen ND; Tran NQT; Le DD; Nguyen QHV; Cao TN (Dove Medical Press, 2023)
Minh Tam Le,1,2 Nguyen Dac Nguyen,1,2 Nhu Quynh Thi Tran,1 Duong Dinh Le,3 Quoc Huy Vu Nguyen,2 Thanh Ngoc Cao1,2 1Center for Reproductive Endocrinology and Infertility, Hue University of Medicine and Pharmacy, Hue University, Hue, Vietnam; 2Department of Obstetrics and Gynecology, Hue University of Medicine and Pharmacy, Hue University, Hue, Vietnam; 3Department of Public Health, Hue University of Medicine and Pharmacy, Hue University, Hue, VietnamCorrespondence: Minh Tam Le, Center for Reproductive Endocrinology and Infertility, Hue University of Medicine and Pharmacy, Hue University, 06 Ngo Quyen street, 53000, Vietnam, Email leminhtam@hueuni.edu.vnObjective: This study aimed to identify the factors that influence follicular output rate (FORT) and follicle-to-oocyte index (FOI) among infertile Vietnamese women, as described by the Poseidon classification of poor responders.Methods: This cross-sectional analysis includes women who received IVF/ICSI treatment at Hue University Hospital, Vietnam, between January 2017 and December 2019. The study population was divided into four groups: Group 1 (age < 35, AFC ≥ 5 and AMH ≥ 1.2 ng/mL, number of oocytes retrieved in the previous cycle ≤ 9), group 2 (age ≥ 35; AFC ≥ 5 and AMH ≥ 1.2 ng/mL, number of oocytes retrieved in the previous cycle ≤ 9), group 3 (age < 35; AFC < 5 and/or AMH < 1.2 ng/mL) and group 4 (age ≥ 35; AFC < 5 and/or AMH < 1.2 ng/mL). All of the patients underwent controlled ovarian stimulation utilizing GnRH antagonist.Results: A total of 243 cases were recruited into groups 1 (n = 44), 2 (n = 33), 3 (n = 54), and 4 (n = 112). There were statistically significant differences between the four groups in terms of age, infertility type, menstrual cycle, body mass index (BMI) and waist-hip ratio (WHR), endocrine tests, and total retrieved oocytes (p 0.05). The average number of oocytes per participant was 7.27, with the highest number occurring in group 1 (10.77) and the lowest occurring in group 4 (5.59). There was a relationship between FORT and BMI (ß: − 0.146, p=0.039), FSH starting dose (ß: 0.146, p=0.030), and AMH (ß:0.166, p=0.015). No statistically significant correlation was detected between FOI and other variables.Conclusion: The starting dose of FSH for ovarian stimulation and AMH concentration were positively associated with FORT in individuals with a poor prognosis, whereas BMI was negatively correlated with FORT; No other parameters were found to correlate with FOI.Keywords: follicular output rate, FORT, follicle-to-oocyte index, FOI, Poseidon, ovarian response